Poonam Smith-Sreen. Accountability in Development Organisations: Experiences of Women s Organisations in India. New Delhi: Sage Publications, 1995.297 pp.Hardcover. Indian Rs 295.00. (The Pakistan Development Review, 1995)
There has been a transition in NGO actIVItIes over time, from the basic welfare orientation to various fields of development. This has been mainly due to the failure of the previous development strategies that emphasised on rates of economic growth, on the assumption that the top-down approach would initiate the process of trickle-down benefits to the poor. The assumed linkages were conceived without a knowledge of the working of the inter-linkages of cultural, social, political, and economic structural processes which led to the failure of such strategies. There appeared to be a need to evolve a workable methodology of development which could replace the top-down strategy. As a consequence of this search, a strategy of grassroots mobilisation of the recipient population was formulated so that they could take part in the process of development in terms of problem identification, project implementation, and its monitoring and evaluation. This strategy is popularly known as community participation. There are two important elements in this participatory approach: a two-way active communication between the community and the NGO to build trust and understanding, and the empowerment of the community towards decision-making for their own needs. This participatory approach is still viable and is a source of social change and development in many countries. The author of this book promises an advancement in this type of development strategy and suggests an alternative model and its method of accountability.